# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {1}{x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{y-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -2 y+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y+x
\] |
✓ |
✓ |
|
\[
{}x \,{\mathrm e}^{y}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime }+y^{2} = -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1-x y}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y \left (y+2 x \right )}{x \left (x +2 y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{1-x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+4 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x -1}+x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\sin \left (x^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x}+{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \cot \left (x \right )+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x -y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y \left (1-y\right )-2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-y^{3}\right )-3 y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 x -1\right )+x \left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{-x^{2}+1}+\sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{-x^{2}+1}+\sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{-x^{2}+1}+\sqrt {x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {3 x^{2}}{2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {3 x^{2}}{2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {3 x^{2}}{2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {3 x^{2}}{2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sqrt {y}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {\left (y+2\right ) \left (y-1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }-2 y^{\prime }+4 y = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime \prime }+x y^{\prime } = 4
\] |
✓ |
✓ |
|
\[
{}x \left (x -3\right ) y^{\prime \prime }+3 y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}x \left (x -3\right ) y^{\prime \prime }+3 y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}\sqrt {1-x}\, y^{\prime \prime }-4 y = \sin \left (x \right )
\] |
✗ |
✓ |
|
\[
{}\left (x^{2}-4\right ) y^{\prime \prime }+y \ln \left (x \right ) = x \,{\mathrm e}^{x}
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime \prime }-{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 31
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 27 x +18
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = -3 x -\frac {3}{x}
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }+6 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+8 y^{\prime \prime }-8 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|